2019
DOI: 10.1111/exd.13821
|View full text |Cite
|
Sign up to set email alerts
|

The impact of carbonylated proteins on the skin and potential agents to block their effects

Abstract: Carbonylated proteins (CPs) are synthesized by reactions between amino groups in proteins and reactive aldehyde compounds (RAC) yielded from lipid peroxidation initiated by reactive oxygen species (ROS). In the skin, CPs are detected in a higher frequency at sun‐exposed sites of the skin in elderly subjects. Since CPs in the stratum corneum (SC) have been reported to correlate with skin water content and transepidermal water loss, it is considered that the accumulation of CPs in the SC involves the loss of ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…On the other hand, the synthesis of CPs, which are also termed lipid-peroxidation end-products, is initiated by aldehyde compounds yielded by lipid peroxidation by ROS 21 . In a previous study, we found that CP-BSA elevates intracellular levels of ROS in fibroblasts, and results in the accumulation of CPs in fibroblasts 6 . The process of CP accumulation is considered to result in the generation of aldehyde compounds such as acrolein.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…On the other hand, the synthesis of CPs, which are also termed lipid-peroxidation end-products, is initiated by aldehyde compounds yielded by lipid peroxidation by ROS 21 . In a previous study, we found that CP-BSA elevates intracellular levels of ROS in fibroblasts, and results in the accumulation of CPs in fibroblasts 6 . The process of CP accumulation is considered to result in the generation of aldehyde compounds such as acrolein.…”
Section: Discussionmentioning
confidence: 81%
“…The cellular functions of fibroblasts can be modulated by surrounding CPs and may cause some problems in the metabolism of the dermal matrix. In fact, our previous study suggested the possibility that CP-BSA, which is a model of extracellular soluble CPs, promotes the degradation of dermal matrix proteins by MMP-1 and IL-8/ CXCL8 that are upregulated at the mRNA expression level 6 . MMP-1 is a critical enzyme that cleaves fibrillar type I collagen, and IL-8/CXCL8 is an important chemokine that recruits neutrophils that produce elastase in the dermis 10 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, CPs are regarded as a footprint of higher oxidation levels. Furthermore, our recent study reported that CPs enhance the biosynthesis of MMP-1 through the elevation of intracellular ROS 10 . These facts indicate the importance of reducing levels of ROS in order to ameliorate the deleterious changes of collagen mediated by UVA.…”
Section: Introductionmentioning
confidence: 95%